The Propagation of Dakwah in Multimedia Era - Farhan Bt Yusof (Universiti Sains Islam Malaysia, 2010)
This research is about the multimedia technology participation of Da'wah in Islamic Da'wah propagation. This research title "The Propagation of Da'wah in Multimedia Era" is a research topic to search about the applied of multimedia technology in Da'wah propagation in this globalization era nowadays. This research project is discussed about six chapters that are interconnected with the topic. The objective of this research is to comprehend and searching about multimedia as a Method(wasi1ah)in Da'wah propagation. Primary data (questionnaire) and Secondary data (books, journal and newspaper) are the tools employed for data gathering purposes. First chapter are discussed about research background, objective, problem statement, scope, Da'wah definition and Multimedia definition. Second chapter are discussed about literature review detailed and in third chapter, the discussion is about research methodology. In fourth chapter, it discusses about the Findings. While, for fifth chapter is analysis data and it discussion detailed and lastly, in sixth chapter, its discussion is about the conclusion and recommendation about this topic research.